The GeoJournal Library
DOI: 10.1007/978-1-4020-5648-2_3
|View full text |Cite
|
Sign up to set email alerts
|

Driving Forces of Landscape Change in The Urbanizing Limmat Valley, Switzerland

Abstract: This research aims to identify the driving forces that changed the Limmat Valley west of Zurich from a traditional agricultural valley in 1930 to a suburban region of the city of Zurich in 2000. The landscape changes are quantified based on the comparison of historical maps from 1930, 1956, 1976 and 2000. All individual changes, relating to new or disappeared landscape elements, were linked to a set of one to fourteen critical driving forces. Such an analytical and systematic study of driving forces, and spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…The author of this study suggested that new housing might be more likely to be built inside the existing urbanised area. The existing spatial configuration has been recognised as an important driver of urbanisation in Switzerland as well (Hersperger and Bürgi, 2007).…”
Section: Built-up Areamentioning
confidence: 99%
“…The author of this study suggested that new housing might be more likely to be built inside the existing urbanised area. The existing spatial configuration has been recognised as an important driver of urbanisation in Switzerland as well (Hersperger and Bürgi, 2007).…”
Section: Built-up Areamentioning
confidence: 99%
“…Five major types of driving forces are identified: political, economic, cultural, technological, and natural/spatial driving forces (Brandt et al, 1999;Bürgi et al, 2004;Hersperger and Bürgi, 2007). The economic driving forces include consumer demands, market structure and structural changes, as well as governmental subsidies and incentives.…”
Section: Introductionmentioning
confidence: 99%
“…However, the insignificant influence of the ethnicity (e.g., percent Australian) factor falsified the cultural hypothesis of landcover changes in this context (Bürgi et al, 2004;Hersperger & Bürgi, 2007;Zeug & Eckert, 2010). This is also true in case of technological (access to motorways) and economic (access to CBD, rental values) drivers.…”
Section: Discussionmentioning
confidence: 91%
“…Based on a prospective analysis, that study also found that the loss of important habitats including areas of high ecological significance within the urban footprint is highly likely due to increased pressures to develop lands for urban uses within this designated area. These studies, therefore, highlight the need for a critical analysis of driving forces associated with land-cover changes, and to develop land use policies accordingly so that the ecologically sensitive areas are protected from urban invasion (Hersperger & Bürgi, 2007).…”
Section: Introductionmentioning
confidence: 99%